Comparative analysis of pharmacists' views on telepharmacy in the Republic of Serbia and the Republic of Slovenia - Ilkić, Jovana; Obradović, Dragiša; Milošević Georgiev, Andrijana; Marinković, Valentina; Tadić, Ivana (Archives of Pharmacy, 2022)
Telepharmacy impacts pharmacists’ involvement in healthcare provision and health care outcomes. This service was implemented in Slovenia since September 2020, opposite to Serbia where this service is not yet implemented. The objective of this study was to compare views of community pharmacists from Serbia and Slovenia in regards to their understanding of the concept of telepharmacy, perceived risks and facilitators, as well as views on overall capacity to implement such services. Semi-structured interviews with community pharmacists were conducted in Slovenia and Serbia from October 2020 to March 2021. Interviews were transcribed ad verbatim, coded, thematically analysed and results were compared for each major emerged theme. In total, 33 community pharmacists accepted to participate (10 from Slovenia and 23 from Serbia). Pharmacists from both countries expressed great interest, motivation and understanding of the concept of telepharmacy. Participants agreed that the services should be charged and remunerated mostly by health insurance funds, and complement the provision of pharmaceutical care in person. They both shared doubts regarding adequacy of pharmacists’ involvement in provision of healthcare, recognising telepharmacy as a tool to enhance it. Participants from Slovenia expressed concerns regarding standardisation, regulations and personal data protection surrounding telepharmacy. On the other hand, participants from Serbia believed that implementing telepharmacy is not yet possible due to lacking regulatory, financial and organisational infrastructure. Slovenian telepharmacy service model may present a good example for profound understanding of facilitators, risks and barriers related to development and implementation of a new pharmacy service in Serbia.